TELEVISI PUBLIK LOKAL SEBAGAI RUANG PUBLIK DAN MEDIA PEMBANGUNAN PARTISIPATIF - Aries Aries (Universitas Serang Raya, 2017)
Regional public television is a certainty, as the public sphere which disseminates the regional potency, local wisdom, motivation and awareness raising community to enhance competitiveness, independent and participate in regional development. Inside the broadcasting regulation of Indonesia, regional public television is called Lembaga Penyiaran Publik Lokal Televisi. The opportunities for the formation of regional public television in Banten province is very potential, because in the province of Banten has not yet own station TVRI itselfs, but that is still manage with TVRI Station Special Capital City of Jakarta. Diversity of Banten's culture and local language are a great potential for regional public television to make broadcasts program on several sub-languages in Banten province. However, the main issue in revision broadcasting regulation of Indonesia is no longer focused on the diversity of content and diversity of ownership. The substance of the regulations on the establishment of regional public television is no longer contained in the draft revision of the broadcasting law of Indonesia. In other side, regional peoples has a right to get localy information, not only followed hegemony’s preference and standard of Jakarta’s value. Indonesia is not only Jakarta. Regional peoples needs more quality broadcasting content as a form of representation of cultural identity; broadcasting program that contain a variety of content that can raise public awareness collectively to preserve culture values and perform positive social actions through regional public television.